2000
DOI: 10.1001/archotol.126.8.969
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Cochlear Enhancement on Magnetic Resonance Imaging in Patients With Autoimmune Sensorineural Hearing Loss

Abstract: No correlation was found between the presence of antibodies to inner ear antigen in patients with hearing loss and cochlear enhancement on MRI scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…These were based on a few cases that demonstrate this alteration. 22 47 We believe the discrepancy between our findings and the literature could be justified with examination after the start of corticosteroids therapy and the methodology of accomplishment and different analysis. …”
Section: Discussioncontrasting
confidence: 60%
“…These were based on a few cases that demonstrate this alteration. 22 47 We believe the discrepancy between our findings and the literature could be justified with examination after the start of corticosteroids therapy and the methodology of accomplishment and different analysis. …”
Section: Discussioncontrasting
confidence: 60%
“…They concluded that MRI was not helpful in diagnosing or managing autoimmune sensorineural hearing loss. 8 However, the clinical utility of high-resolution MRI studies of the inner ear has been well established for threedimensional, gradient-echo sequences, 9,10 two-dimensional sequences, 11 and three-dimensional, fast spin-echo sequences. 12 Compared with two-dimensional studies, three-dimensional studies are useful for assessing inner-ear involvement; 13 T2-weighted, fast spin-echo MRI is valuable for assessing the extent of inner-ear damage.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Interestingly, in a study of 35 patients with confirmed autoimmune sensorineural HL using the 68 kD protein, none of these patients with previously unoperated ears showed evidence of intralabyrinthine enhancement. 11 Labyrinthine enhancement is also rare in viral neuronitis associated with vertigo alone. 12 Our patient had the rare finding of intense labyrinthine enhancement associated with audiovestibular complaints with subjective, objective, and radiologic improvement after systemic antiinflammatory treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%